Effect of lipanthyl on mRNA expression of endothelin-1 and nitric-oxide synthase in atherosclerotic vessel wall in rabbits - Xie Mei-Lin; Gu Zhen-Lun; Chen Ke-Ji; Zhou Wen-Xuan; Guo Ci-Yi (Acta Pharmacologica Sinica, 2016)
"AIM: To study the mechanism of regression of atherosclerosis (AS) by lipanthyl. METHODS: Experimental atherosclerotic rabbits created by damaging the abdominal aortic endothelium and feeding with high fat diet for 8 wk were then treated with lipanthyl 15 mg.kg-1.d-1 for 16 wk. Expression of endothelin (ET)-1 mRNA and nitric oxide synthase (NOS) mRNA in atherosclerotic vessel wall was measured by in situ hybridization and reverse transcription polymerase chain reaction (RT-PCR), respectively. RESULTS: After lipanthyl administration for 16 wk, ET-1 mRNA expression was reduced, and integral optical density (IOD) and area of hybridization granule were observed to be (49,113 +/- 16,868) and (2448 +/- 621) micron 2 in lipanthyl group and (65,188 +/- 10,113) and (3028 +/- 352) micron 2 in atherosclerotic group, respectively. Regarding inducible NOS mRNA expression, IOD and area were decreased by 25.5% and 53.3%, respectively, whereas endothelial NOS mRNA expression was increased. CONCLUSION: Restoration of the disturbed ET-1 mRNA/NOS mRNA balance by lipanthyl might be one of its mechanisms leading to regression of atherosclerosis."